Treatment of avascular necrosis of the humeral head: postoperative results and a proposed modification of the classification - Schmalzl, Jonas; Graf, Annika; Kimmeyer, Michael; Gilbert, Fabian; Gerhardt, Christian; Lehmann, Lars (BMC musculoskeletal disorders, 2022)
Avascular necrosis of the humeral head after proximal humeral fracture i.e. type 1 fracture sequelae (FS) according to the Boileau classification is a rare, often painful condition and treatment still remains a challenge. This study evaluates the treatment of FS type 1 with anatomic and reverse shoulder arthroplasty and a new subclassification is proposed. This single-center, retrospective, comparative study, included all consecutive patients with a proximal humeral FS type 1 treated surgically in a four-year period. All patients were classified according to the proposed 3 different subtypes. Constant score (CS), Quick DASH score, subjective shoulder value (SSV) as well as revision and complication rate were analyzed. In the preoperative radiographs the acromio-humeral interval (AHI) and greater tuberosity resorption were examined. Of 27 with a FS type 1, 17 patients (63%) with a mean age of 64 ± 11 years were available for follow-up at 24 ± 10 months. 7 patients were treated with anatomic and 10 with reverse shoulder arthroplasty. CS improved significantly from 16 ± 7 points to 61 ± 19 points (p < 0.0001). At final follow-up the mean Quick DASH Score was 21 ± 21 and the mean SSV was 73 ± 21 points. The mean preoperative AHI was 9 ± 3 mm, however, 8 cases presented an AHI < 7 mm. 4 cases had complete greater tuberosity resorption. The complication and revision rate was 19%; implant survival was 88%. By using the adequate surgical technique good clinical short-term results with a relatively low complication rate can be achieved in FS type 1. The Boileau classification should be extended for fracture sequelae type 1 and the general recommendation for treatment with hemiarthroplasty or total shoulder arthroplasty has to be relativized. Special attention should be paid to a decreased AHI and/or resorption of the greater tuberosity as indirect signs for dysfunction of the rotator cuff. To facilitate the choice of the adequate prosthetic treatment method the suggested subclassification system should be applied.